“Conductas alimentarias adictivas, alteraciones cognitivas y susceptibilidad genética como factores de riesgo de la obesidad”. - Avitia, Graciela Cristina (Universidad Autónoma de Ciudad Juárez, 2021)
Currently, Mexico represents one of the first places in obesity and overweight prevalence. The caloric intake, addictive eating behavior, cognitive performance and genetic susceptibility are obesity related factors. Therefore, the aim of this study is to identify obesity risk factors to establish the foundations for a predictive, integral and multidisciplinary scheme, involving neuropsychological, psychological, nutritional and genetic elements. Method: The sample includes 159 subjects between ages 20 and 42. To avoid endogamy, direct relatives were not included. Clinic, dietetic, anthropometric, genetic and neuropsychological studies were performed. Results and conclusions: Significant differences between the obese and normal weight groups on the caloric intake were not found. The obese and normal weight groups manifested craving eating behaviors, but not the overweight group. Overeating questionnaire and cognitive performance results were consistent among samples divided by BMI, BGP and waist circumference. The genetic study objectives relates more to the cognitive performance rather than the addictive behaviors and obesity. It was possible to determined that the A1 allele of the Taq1 polymorphism is not a risk factor for obesity, but the sugar and fat consumption, the lose weight motivation, the rationalizations and the lack of control over food are.